Tim-3 Expression and MGMT Methylation Status Association With Survival in Glioblastoma - Ji Zhang; Ke Sai; Xiao li Wang; Sheng quan Ye; Li jiao Liang; Yi Zhou; Zhi jie Chen; Wan-Ming Hu; Jian min Liu (Frontiers Media S.A., 2020)
BackgroundA profound understanding of the molecular landscape of glioblastoma multiforme (GBM) will make it possible to develop better and more intelligent therapies directed toward specific molecular targets and may one day yield better prognostic capabilities. Immune checkpoint molecules have inspired the emergence of immune checkpoint-targeting therapeutic strategies. However, the prognostic significance of the immune checkpoint molecule T cell immunoglobulin mucin-3 (Tim-3) on tumor-infiltrating immune cells (TIICs) and O-6-methylguanine-DNA methyltransferase (MGMT) promoter methylation status has not yet been fully elucidated. We aimed to develop an MGMT promoter methylation status-associated immune prognostic signature for GBM.Patients and MethodsA total of 84 patients with newly diagnosed GBM were included in this study. MGMT promoter methylation status was retrospectively analyzed, and the expression level of Tim-3 was investigated using immunohistochemistry (IHC). The correlation between Tim-3 expression combined with MGMT promoter methylation status and prognosis was explored.ResultsTim-3 expression varied in GBM patients. Mesenchymal expression of Tim-3 in GBM tissues was present 73.81% (62/84) of patients, and these were subdivided into groups based on low 15.48% (13/84), moderate 7.14% (6/84), or strong expression 51.19% (43/84). Forty-eight patients had tumors that tested positive for MGMT promoter methylation, while the remaining 36 patients tested negative.ConclusionsWe profiled the immune status of MGMT promoter methylation in GBM and established a local immune signature for GBM that could independently identify patients with a favorable prognosis, indicating a relationship between prognosis and GBM immune signature. MGMT promoter methylation with lower Tim-3 expression was significantly associated with better survival.